2021
DOI: 10.1007/s00464-021-08859-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of long-term survival in patients with severe comorbidities after endoscopic submucosal dissection for esophageal squamous cell carcinoma

Abstract: Background: Endoscopic submucosal dissection (ESD) is becoming widely popular as a less invasive treatment option for superficial esophageal squamous cell carcinoma.However, data on long-term survival after esophageal ESD in patients with severe comorbidities are limited. This study aimed to evaluate long-term survival after ESD in such patients.Methods: Altogether, 584 consecutive patients underwent esophageal ESD at our institution from May 2004 to September 2016. Based on the American Society of Anesthesiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…Instead, the mortalities could be related to the exacerbation of comorbidities, such as pulmonary, cardiovascular, and cerebrovascular diseases, that existed before colorectal ESD. Similar results were demonstrated for the long‐term outcomes of gastric and esophageal ESD in patients with severe comorbidities categorized according to the ASA‐PS classification 26,27 …”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Instead, the mortalities could be related to the exacerbation of comorbidities, such as pulmonary, cardiovascular, and cerebrovascular diseases, that existed before colorectal ESD. Similar results were demonstrated for the long‐term outcomes of gastric and esophageal ESD in patients with severe comorbidities categorized according to the ASA‐PS classification 26,27 …”
Section: Discussionsupporting
confidence: 74%
“…Similar results were demonstrated for the long-term outcomes of gastric and esophageal ESD in patients with severe comorbidities categorized according to the ASA-PS classification. 26,27 According to previous reports on the normal development of CRC, adenomas with an average size of 11.1 mm developed into advanced cancer in an average observation period of 64.5 months. 28 Considering this report, CEN measuring >20 mm, for which colorectal ESD is indicated, may develop into advanced cancers affecting the patient's prognosis in approximately 4-5 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many patients with non-curative ER for SESCC die of non-ESCC-related causes [ 28 ]. Several retrospective studies have reported the prognostic factors in patients with ER for SESCC [ 49 , 50 , 51 , 52 , 53 , 54 ] ( Table 3 ), but the study populations and significant factors, except the Charlson comorbidity index (CCI), which is a 19-comorbidity tool with weighted points [ 55 ], differed across studies. Only one study evaluated the prognostic factors in patients with non-curative ER for SESCC [ 54 ].…”
Section: Non-curative Er For Sesccmentioning
confidence: 99%
“…In a Japanese report, the frequency of ESCC development was the highest in the middle thoracic esophagus (Mt), followed by the lower thoracic esophagus (Lt), and the upper thoracic esophagus (Ut) [5]. Although other studies have reported similar results in terms of the longitudinal location of ESCC lesions, there have been few reports on the frequency of ESCC lesions based on the circumferential location [5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%